2018
DOI: 10.1007/s11270-018-3702-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential Tolerance to Lead and Cadmium of Micropropagated Gypsophila fastigiata Ecotype

Abstract: In vitro techniques may provide a suitable tool for effective propagation and conservation of plant species representing various ecological niches. The elaboration of such protocols is also prerequisite for selection of heavy-metal-tolerant plant material that could be afterwards used for restoration or remediation of polluted sites. In this study, culture protocol for Gypsophila fastigiata propagation was developed. The highest multiplication coefficient, which reached 6.5, and the best growth parameters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 42 publications
(48 reference statements)
1
9
0
1
Order By: Relevance
“…In our study, we also tested the medium with calcium gluconate to increase calcium supplementation, an excess content of which was noted in wastes obtained from Zn-Pb ores exploitation and processing . Although the medium with an increased amount of Ca ions was the most effective for in vitro propagation of other calamine ecotypes such as Gypsophila fastigiata (Muszyńska et al 2018b) and Dianthus carthusianorum also from Caryophyllaceae family, such an application to both metallicolous and non-metallicolous ecotypes of S. vulgaris did not bring satisfactory effects. In all the abovementioned cases, the morphogenetic response of cultures depended on the S. vulgaris ecotype.…”
Section: Optimization Of Shoot Culture Protocolmentioning
confidence: 96%
See 1 more Smart Citation
“…In our study, we also tested the medium with calcium gluconate to increase calcium supplementation, an excess content of which was noted in wastes obtained from Zn-Pb ores exploitation and processing . Although the medium with an increased amount of Ca ions was the most effective for in vitro propagation of other calamine ecotypes such as Gypsophila fastigiata (Muszyńska et al 2018b) and Dianthus carthusianorum also from Caryophyllaceae family, such an application to both metallicolous and non-metallicolous ecotypes of S. vulgaris did not bring satisfactory effects. In all the abovementioned cases, the morphogenetic response of cultures depended on the S. vulgaris ecotype.…”
Section: Optimization Of Shoot Culture Protocolmentioning
confidence: 96%
“…The seedling shoots bearing an apical meristem were placed onto MS basal medium salts and vitamins supplemented with sucrose (20 g l −1 ). The composition of PGR and others additives was chosen on the basis of previously elaborated protocols for specific S. vulgaris ecotypes or other taxonomically related species from Caryophyllaceae (Hanus-Fajerska 2011; Muszyńska et al 2018b). The assumption of this experimental stage was to obtain a comparable growth of all studied S. vulgaris ecotypes.…”
Section: Shoot Multiplication Protocolmentioning
confidence: 99%
“…Studies on metal-tolerant and metal-sensitive plant genotypes, ecotypes and species revealed that tolerant variants often exhibit constitutively higher antioxidant activity and accumulation of antioxidative compounds (Giannakoula et al 2010;Martins et al 2013;Zhou et al 2017;Muszyńska et al 2018b;Ferrer et al 2018). In D. jasminea treated with HM, irrespectively of treatment duration, antioxidant machinery was significantly reorganized.…”
Section: Major Players Of Heavy Metal Acclimation In D Jasmineamentioning
confidence: 99%
“…It is justi ed to introduce this species to in vitro cultures, which are reliable source of plants for gardening but applied primarily for protection purposes. The constant progress in the technology of micropropagation enables faster and effective obtaining of balanced vegetative offspring in comparison to the results of classic reproduction methods (Hanus-Fajerska et al 2019;Muszyńska et al 2018;Philips and Garda 2019). Techniques of culturing tissues and organs in vitro allow regenerating numerous micro-plantlets under controlled aseptic conditions, from one donor plant or from its fragment.…”
Section: Introductionmentioning
confidence: 99%